Improving community connection to its youth: the case of Wabaunsee county - Amick, Abby L. (Kansas State University, 2011)
Population out-migration from rural communities has caused significant distress in the Midwest of the United States. This distress comes from loss of the communities’ human capital which supports its economic well being. For example, the declining human capital implies lack of employees and consumers to support local business and lower populations that lead to consolidation of schools and services as well as increased per capita costs for these services. Population loss is caused by a variety of reasons, the most discussed being lack of economic opportunities for young people in these small and rural communities. This thesis sought to increase appreciation of the problem by focusing on a single county in Kansas, Wabaunsee County, and assessing the factors that influenced out-migration decisions of its youth. The hypothesis was that understanding these factors and their strength would provide local policy makers with the tools to intervene in the dimensions of the problem of out-migration long before it happens. The data was drawn from a survey of the population of high school students and covered their perspectives about their community and their future location plans. The total number of respondents to the survey was 172, and of these, only 12 percent totally agreed that at least one adult (not parent) has talked to them about opportunities that would encourage them to return home after their post high school or college education. Only about 10 percent totally agreed that there are opportunities in their community for young people to work with adults. These results provide an opportunity for policy makers to engage adults in the community to provide mentorship opportunities for the community’s young people. While the majority of the respondents indicated going to college, only 11 percent indicated that they would return to live and work in Wabaunsee County after graduation. An even lower percentage of respondents indicated retiring in Wabaunsee County when asked to “think way into the future” and indicate whether they would like to retire in the country. The results indicate that the most critical variables influencing respondents’ intent to return after their education included community connection, their age and the existence of a business connection in the county. For example, the relative risk ratio (RRR) for those with community connections was 35 times as high as those without any community connection in their intent to return after college. Similarly, those with business interest in Wabaunsee County with interest in coming back after college exhibited a RRR of 345.15. Similar indicators were found for intentions to retire in Wabaunsee County. It is obvious that the community cannot keep all of its young people. Indeed, it does not want to keep all of them if these young people are going to achieve their personal excellence. However, the community’s leadership can work with local businesses to provide the youth with clear and compelling connections to local and family businesses to increase their community connections. The results of this research indicate that these stronger ties would increase the likelihood that these young people would return. Their return, given the historical trends, would signify a break from the past and contribute to an arrest of the declining population and, hopefully, contribute to an alleviation of the challenges associated with declining population in these small communities.
Keywords: Community development; Youth; Economic development; Rural; Area Planning and Development (0341); Economics (0501); Entrepreneurship (0429)